Evaluation of public health interventions from a complex systems perspective: A research methods review. (March 2021) - McGill, Elizabeth; Er, Vanessa; Penney, Tarra; Egan, Matt; White, Martin; Meier, Petra; Whitehead, Margaret; Lock, Karen; Anderson de Cuevas, Rachel; Smith, Richard; Savona, Natalie; Rutter, Harry; et al.
Abstract: Introduction: Applying a complex systems perspective to public health evaluation may increase the relevance and strength of evidence to improve health and reduce health inequalities. In this review of methods, we aimed to: (i) classify and describe different complex systems methods in evaluation applied to public health; and (ii) examine the kinds of evaluative evidence generated by these different methods. Methods: We adapted critical review methods to identify evaluations of public health interventions that used systems methods. We conducted expert consultation, searched electronic databases (Scopus, MEDLINE, Web of Science), and followed citations of relevant systematic reviews. Evaluations were included if they self-identified as using systems- or complexity-informed methods and if they evaluated existing or hypothetical public health interventions. Case studies were selected to illustrate different types of complex systems evaluation. Findings: Seventy-four unique studies met our inclusion criteria. A framework was developed to map the included studies onto different stages of the evaluation process, which parallels the planning, delivery, assessment, and further delivery phases of the interventions they seek to inform; these stages include: 1) theorising; 2) prediction (simulation); 3) process evaluation; 4) impact evaluation; and 5) further prediction (simulation). Within this framework, we broadly categorised methodological approaches as mapping, modelling, network analysis and 'system framing' (the application of a complex systems perspective to a range of study designs). Studies frequently applied more than one type of systems method. Conclusions: A range of complex systems methods can be utilised, adapted, or combined to produce different types of evaluative evidence. Further methodological innovation in systems evaluation may generate stronger evidence to improve health and reduce health inequalities in our complex world. Highlights: Public health evaluators are interested in applying a complex systems perspective. There is uncertainty about which methods to use and the findings they produce. We reviewed the methods of complex systems evaluations in public health. We developed a framework for complex systems methods and evaluation stages. Further methodological development in this field is required.